2006
DOI: 10.1016/j.virol.2005.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of cellular immune responses elicited by a polyvalent DNA prime/protein boost HIV-1 vaccine

Abstract: While DNA vaccines have been shown to prime cellular immune responses, levels are often low in nonhuman primates or humans. Hence, efforts have been directed toward boosting responses by combining DNA with different vaccination modalities. To this end, a polyvalent DNA prime/protein boost vaccine, consisting of codon optimized HIV-1 env (A, B, C, E) and gag (C) and homologous gp120 proteins in QS-21, was evaluated in rhesus macaques and BALB/c mice. Humoral and cellular responses, detected following DNA immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 79 publications
2
30
0
Order By: Relevance
“…Recently, we demonstrated that a DNA prime-protein boost immunization strategy was effective in eliciting humoral and CMI responses in both small animals and non-human primates, including sterilizing immunity in a non-pathogenic SHIV model [16][17][18]. Our preclinical study results also indicated that this combination vaccination approach, but not recombinant protein alone, was effective in eliciting NAbs against primary HIV isolates [19], a finding that has been confirmed subsequently by other independent studies [20][21][22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recently, we demonstrated that a DNA prime-protein boost immunization strategy was effective in eliciting humoral and CMI responses in both small animals and non-human primates, including sterilizing immunity in a non-pathogenic SHIV model [16][17][18]. Our preclinical study results also indicated that this combination vaccination approach, but not recombinant protein alone, was effective in eliciting NAbs against primary HIV isolates [19], a finding that has been confirmed subsequently by other independent studies [20][21][22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 75%
“…Although significant progress has been made using DNA immunization to elicit HIV-1-specific CMI in small animals, non-human primates and humans over the past 15 years [12][13][14][15][16]18,[38][39][40][41], there has been no report of using Env DNA immunization to elicit broadly crossreactive antibodies in humans. Levels of anti-Env antibodies elicited in previous DNA vaccine clinical trials were either low or undetectable [42,43], nor was there a clear induction of NAbs against even sensitive viruses [14].…”
Section: Discussionmentioning
confidence: 99%
“…Novel boosting immunogens will undoubtedly be needed to elicit broadly neutralizing antibodies. Further, as reported by others [106,107], boosting with protein can lead to increased and broader cellular and humoral immune responses. The studies reviewed to this point all were conducted with two replicating Ad-recombinant priming immunizations followed by two protein boosts.…”
Section: Continued Investigation Of the Best Combination Of Gene Insesupporting
confidence: 52%
“…The DNA immunization approach was adopted, since conventional protein-based vaccines are usually limited in their ability to raise robust cell-mediated immune responses (33). Moreover, the DNA prime/protein boost regimen is known to elicit both cellular and humoral immunity and has been shown to be effective in vaccination experiments against different pathogens in small animals and nonhuman primates (5,26,39). Finally, DNA immunization could allow the elicitation of an immune response against conformational epitopes (1,32,38).…”
mentioning
confidence: 99%